The genus Anastoechus Osten Sacken, 1877 (Diptera: Bombyliidae) from China, with descriptions of four new species - Yao, Gang; Yang, Ding; Evenhuis, Neal L. (Zootaxa, 2010)
Four new species of the genus Anastoechus from China are described and illustrated, namely: Anastoechus candidus sp. nov., Anastoechus fulvus sp. nov., Anastoechus turriformis sp. nov., and Anastoechus xuthus sp. nov., and six previously known species are redescribed and illustrated, namely: Anastoechus asiaticus Becker, Anastoechus aurecrinitus Yang & Du, Anastoechus chakanus Du et al., Anastoechus chinensis Paramonov, Anastoechus doulananus Du et al., Anastoechus neimongolanus Du & Yang. A key to the species of the genus Anastoechus from China is given.